Prevalence of Mastitis Pathogens and Antimicrobial Susceptibility of Isolates From Cattle and Buffaloes in Northwest of Pakistan - Ali, Tariq; Kamran,; Raziq, Abdur; Wazir, Inamullah; Ullah, Rafi; Shah, Pervaiz; Ali, Muhammad Ijaz; Han, Bo; Liu, Gang (Frontiers in Veterinary Science, 2021)
Mastitis is the most prevalent disease of dairy animals, imparting huge economic losses to dairy industry. There is always a dire need to monitor the prevalence of mastitis, its bacteriology and evaluation of antimicrobial susceptibilities for mastitis control and prevention. Therefore, objectives of this study were to investigate: i) prevalence of mastitis in cattle and buffaloes; ii) identification of bacteria associated with mastitis; iii) antimicrobial susceptibility of bacterial isolates. Milk samples (n=1566) from cattle (n=1096) and buffaloes (n=470) were processed for detection of mastitis using California mastitis test in the year 2018-19. A total of 633 mastitic milk samples were further processed for bacteriology and antimicrobial susceptibility testing by disc diffusion method. Overall, prevalence of clinical and subclinical mastitis was 17% and 57% in both species. Clinical mastitis was higher in cattle (20%) compared to buffaloes (11%), whereas subclinical was higher in buffaloes (66%) than cattle (53%). Besides, month-wise prevalence was higher in hot and humid months in both species. Staphylococci spp. (34%) were the most predominant bacterial isolates from mastitic milk, followed by Escherichia coli (19.4%), Streptococci spp. (9%) and Klebsiella spp. (8%). Most of the bacteria were susceptible to gentamicin (92%) and enrofloxacin (88%), when a panel of 16 different antimicrobials was tested. Nevertheless, most of the isolates were resistant to sulphamethoxazole (99%), lincomycin (98%), oxytetracycline (89%), ampicillin (86%) and doxycycline (85%). This study suggests a high prevalence of staphylococcal mastitis in cattle and buffaloes of Khyber Pakhtunkhwa, mostly susceptible to gentamicin and enrofloxacin.